Evaluation of simple and Cost-Effective DNA preparation and subsequent PCR amplification for clinically relevant mycobacteria (2015)
ABSTRACT : Aim: Slow growth rate in culture renders the traditional isolation, identification, and drug susceptibility testing of clinically important mycobacteria inadequate when there is an urgent need for a precise diagnosis in order to initiate patient treatment. Molecular methods all rely on mycobacterial DNA isolation which in turn has become an essential step of the process. Our study aimed to evaluate DNA isolation protocols from mycobacteria of clinical interest. Methods: Therefore, in order to determine an optimal method we evaluated 8 inexpensive, rapid and easy DNA isolation methods from 30 mycobacterial cultures (10 Mycobacterium tuberculosis and 20 Non-tuberculous Mycobacteria) for subsequent direct detection by PCR. Results: Six of those 8 methods reliably allow the isolation of good DNA yields and quality, the optimal protocol being the one that includes a 1% Triton X-100 lysis solution. Protocols using SDS 1% as a lysis solution did not yield DNA suitable for PCR amplification. Conclusion: Six of the methods we evaluated can easily be implemented in resource limited settings for routine use, potentially contributing to a better management of mycobacterial infections.